NATIONAL IDEA AS THE BASIS OF EDUCATION AND UPBRINGING OF THE YOUNG GENERATION IN THE WORKS OF UKRAINIAN WRITERS OF THE XIX – EARLY XX CENTURY - Slyusarenko, Nina (Mountain School of Ukrainian Carpaty, 2020)
The article emphasizes that a remarkable role in the history of Ukraine in general and in the development of education, in particular, is played by outstanding, patriotic personalities, among whom writers have a special place. The aim of the research is to analyse the development of the national idea as the basis of education and upbringing of the younger generation by Ukrainian writers of the XIX - early XX centuries. For this purpose, the following methods such as the method of historical-logical analysis and systematisation, the search-bibliographic method and the problem-genetic method have been used. It has been revealed that during the period under study the educational sector in our country was developing rapidly. It has been stated that Ukrainian writers (Taras Shevchenko, Ivan Franko, Pavlo Hrabovskyi, Mykhailo Kotsiubynskyi, Lesia Ukrainka, Olha Kobylianska, Olena Pchilka, Liudmyla Starytska-Cherniakhivska and many others) played a significant role in this process, their educational activities and pedagogical views significantly influenced the development of society and they were reflected in the work of educational institutions of different levels. It has been emphasized that the national idea became a cross-cutting line that ran through the works of all Ukrainian writers of the above-mentioned era. It has been concluded that writers in their works described the history, traditions, customs, life of Ukrainian people, their interests, preferences, moral qualities and so on. They stood out for the education of children in their native language, called for the education of their love for the motherland, the national consciousness. The writers not only cared about the fortune of Ukrainian people and the national school, but also called for radical changes in education, tried to improve it, in particular by creating educational literature, outlining the educational ideal, goals and objectives of national education of the younger generation and others. The need for a more thorough study of the heritage of Ukrainian writers of the period under study in further scientific research has been indicated.